2014
DOI: 10.1177/1538192714540531
|View full text |Cite
|
Sign up to set email alerts
|

Challenges, Choices, and Decisions of Women in Higher Education

Abstract: This research examined challenges, choices, and decisions of women professors in higher education. Special attention was given to Latina professors. This article reviewed the literature on established theories of representative bureaucracy and contextualized faculty women, especially Latinas, in this proportional representation framework. Answers were sought to three research questions: Are Hispanic, Black, and Asian women keeping pace with their White peers in higher education; are women as a group in higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Studies have also shown that poor or nonexistent family-friendly policies in academia and lack of mentorship can result in the loss of women faculty at higher levels. [9][10][11] This drop in the number of women faculty is an issue that merits further consideration. Figure 3 illustrates that the greatest representation of Latino engineering faculty hail from Mexico-152 individuals representing 25.9% of total faculty.…”
Section: In Materials Science and Engineering Special Featurementioning
confidence: 99%
“…Studies have also shown that poor or nonexistent family-friendly policies in academia and lack of mentorship can result in the loss of women faculty at higher levels. [9][10][11] This drop in the number of women faculty is an issue that merits further consideration. Figure 3 illustrates that the greatest representation of Latino engineering faculty hail from Mexico-152 individuals representing 25.9% of total faculty.…”
Section: In Materials Science and Engineering Special Featurementioning
confidence: 99%
“…While these types of resources may seem typical, studies indicate that they may not be common. In fact, Latina women seeking employment as professors, experience lack of career mentoring, disparate promotions, and inequitable salaries (Ortega-Liston & Rodriguez-Soto, 2014;Sulé 2011). These research findings highlight the need for higher education leaders and policy makers to advocate for equitable promotions and salaries as well as implement recruitment and retention programs for Mexican American women PSEs.…”
Section: Implications For Post-secondary Education and Researchmentioning
confidence: 93%
“…Compared to Black and Asian women, Latina women are least frequently employed as professors in higher education (American Indian and Pacific Islander women being the least employed women after Latina women). Specific to post-secondary educators, Latino, Black, and Asian compromise 18.9% of PSEs, while Non-Latino Whites compromise 81.1 % of PSEs (Ortega-Liston & Rodriguez-Soto, 2014). These statistics demonstrate the lack of Mexican American women employed as PSEs, thus increasing the need to support those currently employed as PSEs and the need to recruit Mexican American women into this profession.…”
Section: Implications For Post-secondary Education and Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…Women earn more degrees at higher levels than men earn but are not keeping pace with achieving tenure, senior-level positions, or equal pay (Lepkowski, 2009 &Ortega-Liston andSoto, 2014). Determined in this investigation was whether the percentages of female faculty members at the three major faculty ranks at Texas 4-year public institutions changed between the 2003 and the 2014 academic years.…”
Section: Purposementioning
confidence: 99%